Die Psychidenfauna der Republik Zypern (Lepidoptera: Psychidae). - Weidlich, Michael (Contributions to Entomology = Beiträge zur Entomologie, 2015)
In the present paper the knowledge of the bagworm moth of the Republic of Cyprus is discussed. Currently 6 species of this family are known from Cyprus. Also a new species Eumasia cyprianella spec. nov. is described herein. The author visited the island in the years 1998, 1999, 2012 and 2014. First results of the collecting trips were published in 2002, including the first description of Pseudobankesia aphroditae Weidlich & Henderickx, 2002. Morphological and cytochemical (mtDNA) characteristics are addressed and the distribution of Pachythelia villosella (Ochsenheimer, 1910) is discussed. The taxon P. villosella quadratica De Freina, 1983 is reviewed. Further particulars on the biology and ecology of the Psychidae of the Republic of Cyprus Psychidae complete the work.KeywordsRepublic of Cyprus, faunistic review, Eumasia cyprianella spec. nov., Psychidae, Lepidoptera, biology, morphology, history.Nomenclatural Actscyprianella Weidlich, 2015 (Eumasia), spec. n.